2017
DOI: 10.1371/journal.pone.0169596
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Fundus Blood Flow in Normal Individuals and Patients with Internal Carotid Artery Obstruction Using Laser Speckle Flowgraphy

Abstract: PurposeWe investigated whether laser speckle flowgraphy (LSFG) results are comparable in both eyes and whether it is useful in the diagnosis of disparity in ocular ischemic syndrome (OIS) patients.MethodsWe compared the mean blur rate (MBR) value for various fundus regions in both eyes of 41 healthy subjects and 15 internal carotid artery occlusion (ICAO) cases. We calculated the standard value of the Laterality Index (LI), which was the MBR comparison of both eyes in each of the regions, in the control subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
4

Year Published

2018
2018
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 24 publications
1
8
0
4
Order By: Relevance
“…Additionally, the degree of ICA stenosis was 76 %. This finding is similar to that from a previous study in which the degree of the ICA stenosis and the ratio of the affected to the fellow eye was shown to be inversely correlated [17]. In the present case we found a higher level of HbA1c and IOP (50mmHg) caused by rubeosis iridis.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Additionally, the degree of ICA stenosis was 76 %. This finding is similar to that from a previous study in which the degree of the ICA stenosis and the ratio of the affected to the fellow eye was shown to be inversely correlated [17]. In the present case we found a higher level of HbA1c and IOP (50mmHg) caused by rubeosis iridis.…”
Section: Discussionsupporting
confidence: 93%
“…The previous study that used LSFG demonstrated that MBR in the ONH and choroid in the affected eye significantly decreased compared with that in the fellow eye in OIS [17]. However, to the best of our knowledge, the time course of the optic nerve head, choroidal blood flow, and pulse waveform using LSFG in OIS with rubeosis iridis is yet to be investigated.…”
Section: Introductionmentioning
confidence: 90%
“…In our study, we showed that the normal non-anesthetized eyes of rabbits depict a strong correlation with their fellow eyes. A similar study demonstrated a significant correlation of blood flow volume in the normal eyes of healthy human subjects 15 . They found the LI for the entire image to be equivalent to one.…”
Section: Discussionmentioning
confidence: 56%
“…Similarly, Shinohara et al . defined the LI as a ratio of the MBR value of the occluded eye to that of the non-occluded eye to diagnose patients with OIS 15 . In this study, we defined the LI as a ratio of the lower MBR value to the higher MBR value for normal eyes.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, associated diseases such as hypertension and diabetes also contribute to the vessel elasticity impairment 11 . Several studies have reported that carotid artery stenosis due to atherosclerosis results in impaired OBF as measured by using the MBR 12,13 . However, the characteristics of ocular hemodynamic remain unknown.…”
mentioning
confidence: 99%